Managing Grief of Bereaved Families During the COVID-19 Pandemic in Japan - Matsuda, Yoko; Takebayashi, Yoshitake; Nakajima, Satomi; Ito, Masaya (Frontiers in Psychiatry, 2021)
This commentary discussed the psychological issues related to bereavement in the wake of the COVID-19 pandemic. Specifically, we addressed two aspects in the context of Japanese culture. The first relates to the psychological distress of members of the bereaved family who could not visit their loved ones who had COVID-19 before or after their death. The second relates to the bereavement experience of those who were unable to be with their loved ones when the end came, even though they did not have COVID-19, because of restrictions on visiting hospitals. We seek to focus on the need for a support system for bereaved families to help them through the grieving process, and discuss end-of-life care in such circumstances, and in the post-COVID-19 era, as in current day Japan.